La competencia mediática en los perfiles pedagógicos de la profesora Alba Marília (Innovaciones Educativas, 2024)
Media literacy is a challenge and a necessity for teacher education because media content is present in everyday school and social life. Moreover, it is often used or accessed without the necessary knowledge. Therefore, media literacy is fundamental for people to be able to consume and produce content critically and analytically. The aim of this study was to understand the production of content in social media carried out by Professor Alba Marília and its relationship with media literacy. For this purpose, a netnography study was conducted to analyze her most popular YouTube videos and Instagram stories. The comments on the videos in both social networks were analyzed, which, like the interviews, served as a basis for understanding how Ferrés and Piscitelli's (2012) dimensions of media literacy can be observed in the professor's profiles. The results show that the teachers' videos make some dimensions of media literacy explicit, such as language and technology. It can be concluded that Alba Marília, with an accessible pedagogical approach, demonstrates media literacy and commitment to teacher training, enriching activities.
Keywords: tecnología educacional; enseñanza multimedia; formación de profesores; medios sociales; educación de la primera infancia